The long non‐coding RNA MALAT1 promotes ovarian cancer progression by regulating RBFOX2‐mediated alternative splicing. Issue 2 (28th October 2018) - Gordon, Michael A.; Babbs, Beatrice; Cochrane, Dawn R.; Bitler, Benjamin G.; Richer, Jennifer K.
Abstract : Ovarian cancer metastasizes via direct seeding, whereby cancer cells shed from the primary site, resist cell death in the peritoneal cavity, then metastasize to peritoneal organs. We sought to identify molecular mechanisms that facilitate ovarian cancer cell anchorage independent survival. Gene expression profiling was performed on ovarian cancer cells grown in attached or forced suspension culture and confirmed by RT‐qPCR. Anoikis was measured by Caspase 3/7 assay. Since the long non‐coding RNA Metastasis Associated Lung Adenocarcinoma transcript 1 (MALAT1) was among the transcripts most highly increased in forced suspension culture, modified anti‐sense oligonucleotides (ASO) were used to inhibit its expression. Knockdown of RBFOX2 and KIF1B was performed using shRNAs. Publically available datasets were analyzed for association of MALAT1 gene expression with clinicopathological variables. In multiple anoikis‐resistant ovarian cancer cell lines MALAT1 expression increased after 24 and 48 h in forced suspension culture compared to attached culture. High MALAT1 is associated with increased stage, recurrence, and reduced survival in ovarian cancer, and in a small percentage of ovarian cancers MALAT1 is amplified. MALAT1 knockdown resulted in decreased proliferation, invasion, anchorage‐independent growth, and increased anoikis. Suppression of MALAT1 also resulted in decreased expression of RBFOX2, and alternative processing of the pro‐apoptotic tumor suppressor gene KIF1B . RBFOX2 suppression resulted in preferential splicing of the pro‐apoptotic isoform of KIF1B (KIFB1B‐beta) and increased anoikis. The lncRNA MALAT1 facilitates a pro‐metastatic phenotype in ovarian cancer by promoting alternative RNA processing and differential expression of anti‐apoptosis and epithelial to mesenchymal transition (EMT)‐related genes.